Завдання досліджень економічної геології - Бодюк, А.В. (Геологічний журнал, 2010)
Обосновано понятие недро-разведывательного производства, его составляющих. Установлены народно-потребностные, товароведческие, ресурсно-оценочные, природно-ресурсные, недро-производственные, научно-технические, хозяйственные, финансово-фискальные, профессионально-кадровые, эколого-геологические виды исследований; определены их задания. Предложен показатель государственной стоимости месторождений полезных ископаемых. The concept of reconnaissance of production of bov/els of the earth and his constituents is grounded. A consumer, commodity expert, resource evaluation, naturally-resource, production, scientific and technical, economic, financially-fiscal, professionally-skilled, ecological and geological types of researches are determined, their tasks are certain. The index of state cots of deposits of minerals is offered.